Heterogeneous effects of the digital economy on high-quality green development of urban economy and its spatial spillovers: evidence from the Upper Yangtze River Economic Belt - Fan, Qin; Yang, Jie; Song, Yanliang (Frontiers in Sustainable Cities, 2025)
Against the backdrop of deep integration between global digital transformation and sustainable development, the digital economy—with data as its core driver—has reshaped urban development paradigms and emerged as a pivotal force in advancing economic growth and green transformation. The urban agglomerations in the Upper Yangtze River Economic Belt, which balance ecological security and economic growth in western China, provide a strategically significant case for exploring how the digital economy influences high-quality green urban development. Using panel data (2011–2023) from 32 prefecture-level cities in this region, we constructed comprehensive indices to quantify the digital economy and high-quality green development. We applied benchmark regression, quantile regression, and spatial Durbin models to analyze direct effects, mediating pathways, and spatial spillover effects, with robustness validated through variable replacement and sample adjustment, and heterogeneity examined by city scale and resource attributes. The results indicate that the digital economy exerts a stable and positive impact on high-quality green development, a conclusion that remains robust across multiple tests. Innovation capability mediates approximately 20.96% of the total effect. Heterogeneity analysis reveals stronger driving effects in large cities compared to small and medium-sized cities, and in non-resource-based cities relative to resource-based ones. Additionally, the digital economy demonstrates significant spatial spillover effects, fostering coordinated development in neighboring cities, with its most prominent impact on coordinated development among the five sub-dimensions of high-quality green growth. This study confirms that the digital economy serves as a critical new productive force for green transformation. Targeted strategies—including hierarchical enhancement of digital infrastructure, strengthened innovation-mediated mechanisms, mitigation of heterogeneous development dilemmas, and amplification of spatial synergies—offer micro-level evidence and policy insights for underdeveloped regions to advance “digital empowerment + green transformation.”